Identifikasi Sistem Motor DC dan Kendali Linear Quadratic Regulator Berbasis Arduino-Simulink Matlab - Fahmizal, Fahmizal; Fathuddin, Fahmy; Susanto, Rudi (Majalah Ilmiah Teknologi Elektro, 2018)
This paper describes the identification process of DC motor system with experimental technique using indetification tool in Matlab. After the DC motor model system is obtained, the optimal control technique in this case using linear quadratic regulator (LQR) is used to view the system response step. In this research, the motor modification system module with Arduino DC was developed to facilitate in terms of getting the model of DC motor by approaching first and second order models. This module is integrated between Arduino and Simulink Matlab which is used as input-output data acquisition. The result of the system identification process is a model of DC Motor with second order ARX (Auto Regressive Exogenous) modeling. Furthermore, the implementation of LQR control technique with parameter of Q element element is sought by multiplication of transpose matrix C system with matrix C of the system. While the R element matrix in tuning experimentally with value 0.000001. From the test results obtained that LQR control produces a better system response time constant when compared to PID control.